Effectiveness of the Close Collaboration with Parents intervention on parent-infant closeness in NICU - He Felix B; Axelin Anna; Ahlqvist-Bjorkroth Sari; Raiskila Simo; Löyttyniemi Eliisa; Lehtonen Liisa (BMC, 2022)
BackgroundParent-infant closeness during hospital care of newborns has many benefits for both infants and parents. We developed an educational intervention for neonatal staff, Close Collaboration with Parents, to increase parent-infant closeness during hospital care. The aim of this study was to evaluate the effectiveness of the intervention on parent-infant closeness in nine hospitals in Finland.MethodsParents of hospitalized infants were recruited in the hospitals during 3-month periods before and after the Close Collaboration with Parents intervention. The data were collected using daily Closeness diaries. Mothers and fathers separately filled in the time they spent in the hospital and the time of skin-to-skin contact with their infant during each hospital care day until discharge. Statistical analyses were done using a linear model with covariates.ResultsDiaries were kept before and after the intervention by a total of 170 and 129 mothers and 126 and 84 fathers, respectively. Either parent was present on average 453min per day before the intervention and 620min after the intervention in the neonatal unit. In the adjusted model, the increase was 99min per day (p=0.0007). The infants were in skin-to-skin contact on average 76min per day before the intervention and 114min after the intervention. In the adjusted model, skin-to-skin contact increased by 24min per day (p=0.0405).ConclusionThe Close Collaboration with Parents intervention increased parents' presence and skin-to-skin contact in nine hospitals. This study suggests that parent-infant closeness may be one mediating factor explaining benefits of parenting interventions.Trial registrationClinicalTrials.govNCT04635150. Retrospectively registered.